Strategic renewal of hotel industry in developing countries through human capital development, ambidextrous learning and dynamic capabilities - Muhammad Ali; Muhammad Yasir; Abdul Majid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
In recent years, strategic renewal has become a projecting area in contemporary management research. It refers to the process that allow businesses to change their strategic intent, learning and capabilities. This paper seeks to develop a theoretically perspective on the active nature of the association among human capital development and strategic renewal of firm in small scale hotel industry. Moreover, to understand the positive role of human capital development, the current study has also analysed ambidextrous learning as a mediator and the moderating role of dynamic capabilities. Data were collected through questionnaires from 416 managers/owners of small-scale hotels (budget hotels) functioning in the tourist destinations of Pakistan. To analyse the data, hierarchical regression was used which provided very interesting results. This study indicates that human capital development positively predicts strategic renewal. Furthermore, ambidextrous learning mediates the relationship among human capital development and strategic renewal. Moreover, the results confirm that dynamic capabilities reinforce the association of human capital development and strategic renewal. Limited studies provide holistic approach to examine the preconditions for strategic renewal. This study also reveals that development of human capital plays a critical role for strategic renewal in the presence of ambidextrous learning.
Keywords: 330; human capital development; ambidextrous learning; strategic renewal; dynamic capabilities; budget hotels; hotel industry